Rose of Sharon - Thomas Hart Benton (artist):::Creator::::::::::::
Rose of Sharon from the souvenir program for the film, The Grapes of Wrath. Thomas Hart Benton, a native of eastern Oklahoma, was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "Beside them, clinging lightly to the bars, stood Rose of Sharon, and she balanced, swaying on the balls of her feet, and took up the road shock in her knees and hams." p.118